Latest Trends in German Domestic and Foreign Policy (Czech Journal of International Relations, 1998)
Developments in German Politics 2. Edited by Gordon Smith, William E. Paterson andStephen Padgett. Macmillan Press LTD, London 1996, 348 stran, ISBN 0-333-65902-3.